Controllable Synthesis of Mesoporous TiO2 Polymorphs with Tunable Crystal Structure for Enhanced Photocatalytic H2 Production. Issue 31 (8th July 2019) - Xiong, Hailong; Wu, Lanlan; Liu, Yu; Gao, Tunan; Li, Kaiqian; Long, Yan; Zhang, Rui; Zhang, Ling; Qiao, Zhen‐An; Huo, Qisheng; Ge, Xin; Song, Shuyan; et al.
Abstract: Multiphasic titanium dioxide (TiO2 ) possessing abundant heterophase junctions have been widely used for various photocatalytic applications. Current synthesis of multiphasic TiO2 mainly involves the process of thermal treatment and multiple steps of rigorous reactions, which is adverse to controlling the crystal phases and phase ratios of multiphasic TiO2 . Meanwhile, the resulting products have relatively low surface area and nonporous structure. Here, a facile polymer‐assisted coordination‐mediated self‐assembly method to synthesize mesoporous TiO2 polymorphs with controllable heterophase junctions and large surface area by using polyethylenimine as the porogen in an acidic aqueous synthesis system is reported. Using this approach, the crystal phases (triphase, biphase, and monophase) and phase compositions (0–100%) are easily tailored by selecting the suitable acidic media. Furthermore, the specific surface areas (77–228 m 2 g −1 ) and pore sizes (2.9–10.1 nm) are readily tailored by changing the reaction temperature. The photocatalytic activity of mesoporous TiO2 polymorphs is evaluated by photocatalytic hydrogen evolution. The triphasic TiO2 exhibits an excellent photocatalytic H2 generation rate of 3.57 mmol h −1 g −1 as compared to other polymorphs, which is attributed to the synergistic effects of heterophase junctions and mesostructure. The band diagram of possible electron transfer pathway for triphasic TiO2 is also elucidated. Abstract : A facile polymer‐assisted coordination‐mediated self‐assembly allows the synthesis of mesoporous triphase anatase/rutile/brookite TiO2 with controllable heterophase junctions and large surface area. The triphasic TiO2 exhibits an excellent photocatalytic H2 generation rate of 3.57 mmol h −1 g −1 as compared to other polymorphs, which is attributed to the synergistic effects of heterophase junctions and mesostructure.